A tooth of Archaeopterygidae (Aves) from the Lower Cretaceous of France extends the spatial and temporal occurrence of the earliest birds. (May 2017) - Louchart, Antoine; Pouech, Joane
Abstract: The Late Jurassic Archaeopterygidae, comprising the iconic genus Archaeopteryx, is altogether among the earliest, basalmost and best-known Mesozoic avian taxa. The geographic distribution of Archaeopteryx is hitherto restricted to a limited region of southern Germany, probably due to preservation biases. Here we describe a tooth sorted among the more than 35, 000 isolated teeth found by sieving sediments from the Cherves-de-Cognac locality (western France, Lower Cretaceous). This tooth crown is morphologically similar to teeth of the German specimens of Archaeopteryx (sensu lato), despite minor differences. The Cherves-de-Cognac tooth differs much more importantly from all other known taxa. It shares with different specimens of Archaeopteryx the general tooth size, recurved shape affecting apical third of crown, thin apical-mesial carina, constriction at base of crown giving distinctive S shape of distal edge in profile, absence of other ornamentation or serration, and shape of crown section. Incidentally, former assignments of teeth from the Upper Jurassic of Guimarota (Portugal) to cf. Archaeopteryx are unwarranted, as those teeth markedly differ from the Archaeopterygidae in several crucial features. We assign the new tooth to the family Archaeopterygidae, the earliest European birds, making it the first member of the family in Europe outside Germany, and extending its temporal occurrence to the early Cretaceous. Highlights: A tooth from the Lower Cretaceous of France is assigned to the Archaeopterygidae. It is the only record for the family outside southern Germany. It also extends the record younger than the late Jurassic. Purported teeth from Portugal actually do not belong to the Archaeopterygidae.